CROSS INVESTIGATION OF ACADEMIC PERFORMANCE AND CHALLENGES FACED BY CULTURE AND ARTS PERFORMERS - Tabao, Kristel Joy (International Journal of Arts, Sciences and Education, 2022)
As a direct result of their exposure, students have a more comprehensive understanding of the ways in which culture and the arts have the potential to revitalize the human spirit, revive hope, and remind us of the beauty that exists in life. The primary purpose of this investigation is to ascertain whether or not there is a considerable connection between the challenges encountered by the respondents along each of the seven qualities and the degree of academic achievement they have attained. According to the findings of the study, there does not appear to be a significant connection between the challenges that the respondents had in their participation in cultural and artistic activities and their level of academic accomplishment. This lends credence to the idea that the academic success of the respondents is unrelated to the social activities in which they engage. Students who took part in extracurricular activities had, on average, superior educational success, better examination outcomes, and a more positive self-concept. They also scored higher on standardized tests. Students frequently improved their abilities in areas such as leadership and cooperation by participating in college club activities, which also reduced the likelihood of students engaging in a variety of problematic behaviors. Students who participated in college club activities improved their abilities in these areas more frequently.